Between Welfare and Vulnerability: A Critique of Marriage Dispensation in the Probolinggo Religious Court Decree from the Perspective of Maqasid al-Shari'ah and Children's Rights - Fatlala Nur Azizah; Abu Yazid Adnan Quthny; Nina Agus Hariati (STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2026)
The amendment of the Marriage Law through Law Number 16 of 2019, which raised the minimum marriageable age to 19 years, has created a legal paradox in Indonesia. Despite stricter regulations intended to prevent child marriage, requests for marriage dispensation in Religious Courts have significantly increased. This study analyzes the judicial reasoning behind these grants using a qualitative document study and a descriptive-normative approach, specifically focusing on the Probolinggo Religious Court Decree No. 210/Pdt.P/2025/Pa.Probolinggo. The findings indicate that judges often grant dispensations based on the Islamic legal maxim akhaff al-dararain (choosing the lesser of two evils) to prevent perceived social harms such as premarital intimacy or pregnancy. However, from the perspective of Maqasid al-Syari’ah and children’s rights, this study critiques the dominance of short-term welfare considerations over long-term vulnerabilities. The results suggest that current judicial practices often neglect the child's rights to education (hifz al-’aql), reproductive health (hifz al-nafs), and economic stability. The study concludes that a transformation in the judicial approach is necessary, moving from a formal-administrative